Comparing Anal Cancer Screening Algorithms Using Cytology and Human Papillomavirus DNA Testing in 3 High-Risk Populations. (3rd January 2021) - Gaisa, Michael M; Sigel, Keith M; Deshmukh, Ashish A; Lenskaya, Volha; Chan, Courtney A; Silvera, Richard; Winters, John; Liu, Yuxin
Abstract: Background: Screening strategies for high-risk human papillomavirus (hrHPV)-associated anal cancer are evolving. Herein, we compare anal cytology to hrHPV DNA testing and 2 novel cytology/hrHPV cotesting algorithms among 3 high-risk populations. Methods: Anal cytology, hrHPV DNA testing, and high-resolution anoscopy (HRA)-guided biopsy results were analyzed from 1837 participants (1504 HIV-infected men who have sex with men (MSM), 155 HIV-uninfected MSM, and 178 HIV-infected women). Performance to detect histological high-grade squamous intraepithelial lesions (HSIL)/cancer was compared between 4 strategies with distinct HRA referral thresholds: cytology (atypical squamous cells of undetermined significance, ASCUS); hrHPV testing (any hrHPV positive); algorithm A (benign cytology/HPV16/18 positive or ASCUS/hrHPV positive); and algorithm B (benign or ASCUS/hrHPV positive). Results: Histological HSIL/cancer was detected in 756 (41%) participants. Cytology had the lowest sensitivity (0.76–0.89) but highest specificity (0.33–0.36) overall and for each subgroup. Algorithm B was the most sensitive strategy overall (0.97) and for MSM (HIV-infected 0.97; HIV-uninfected 1.00). For women, hrHPV testing and both algorithms yielded higher sensitivity than cytology (0.96, 0.98, and 0.96). Specificity was low for all strategies/subgroups (range, 0.16–0.36). Conclusions: Screening algorithms that incorporate cytology and hrHPV testing significantly increased sensitivity but decreased specificity to detect anal precancer/cancer among high-risk populations. Abstract : Screening strategies for high-risk human papillomavirus (hrHPV)-associated anal cancer are evolving. This study compares the screening performance of anal cytology to hrHPV DNA testing and 2 novel cotesting algorithms among 3 high-risk populations: HIV-positive MSM, HIV-negative MSM, and HIV-positive women.